(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2018)
Cloud computing is Internet ("cloud") based development and use of computer technology ("computing"). It is a style of computing in which dynamically scalable and often virtualized resources are provided as a service over the Internet. Cloud computing uses the internet and the central remote servers to support different data and applications. It is an internet based technology. It permits the users to approach their personal files at any computer with internet access. The cloud computing flexibility is a function of the allocation of resources on authority’s request. Cloud computing provides the act of uniting. Scientific computing in the 21st century has evolved from fixed to distributed work environment. The current trend of CloudComputing (CC) allows accessing business applications from anywhere just by connecting to the Internet. Evidence shows that, switching to CC organizations’ annual expenditure and maintenance are being reduced to a greater extent. However, there are several challenges that come along with various benefits of cloud computing. Among these include securityaspects. Our aim is to identify security challenges for adapting cloud computing and their solutions from real world for the challenge that do not have any proper mitigation strategies identified. This non-existence of global standards and guidelines could be help academics to know the state of practice and formulatebetter methods/standards to provide secure interoperability. The identified cloud computing security challenges and solutions can be referred by practitioners to understand which areas of security need to be concentrated while adapting/migrating to a cloud computing environment.